Le langage des clients difficiles en counseling et en psychothérapie - Lecomte, Conrad (Canadian Journal of Counselling and Psychotherapy, 2007)
The purpose of this article is to examine difficult cases and situations that seem to defy therapists and counsellors. Instead of trying to classify static signs and symptoms of difficult clients into profiles and taxonomies, a conceptual and practical perspective of the nature and the process of client resistance and defenses is offered. Proper intervention and assessment depend upon the therapist's seeing behind the symptom. Appreciating and working in concert with the client's natural healing processes are essential to psychological immunology. Understanding the self protective values of defense mechanisms will allow therapists to appreciate that they serve as servants to, rather than masters of, psychological healing processes. Too often, counsellors and therapists fail to pay attention to the difference between disease process, and self-protective mechanisms. Understanding defenses allow us to empathize and provide language to discuss the interplay of feelings and ideas and ultimately human suffering.